PENGARUH MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS TEKS CERPEN SISWA KELAS XI SMA NEGERI 1 V KOTO KAMPUNG DALAM - Arulina, Syifa; Ayu Gustia Ningsih; Afnita; Mita Domi Fella Henanggil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low short story writing skills of grade XI students at SMA Negeri 1 V Koto Kampung Dalam, where the average student performance had not reached the Minimum Mastery Criteria (KKM) of 75. This study aimed to describe students' short story writing skills before and after the implementation of the Project-Based Learning model assisted by audiovisual media, and to analyze the effect of this model on students' writing skills. This was a quantitative study using an experimental method with a One Group Pretest-Posttest design. The population consisted of all grade XI students, with a sample of 25 students from class XI F6 selected through purposive sampling. Data were collected via short story writing performance tests and analyzed using normality, homogeneity, and hypothesis (t-test) tests. The results showed that the average short story writing score before using the Project-Based Learning model assisted by audiovisual media was 47.88 (Nearly Sufficient), while it increased to 71.38 (More than Sufficient) after the intervention. Hypothesis testing indicated that the t-count was greater than the t-table (7.51 > 1.98), leading to the acceptance of the alternative hypothesis (H1). Thus, it is concluded that the Project-Based Learning model assisted by audiovisual media has a significant influence on the short story writing skills of grade XI students at SMA Negeri 1 V Koto Kampung Dalam.